Edema agudo pulmonar associado à obstrução das vias aéreas. Relato de caso - Bisinotto, Flora Margarida Barra [UNESP]; Cardoso, Ricardo de Paula; Abud, Tânia Mara Vilela [UNESP] (Elsevier, 2008)
BAKGROUND AND OBJECTIVES: Negative pressure pulmonary edema has been defined as non-cardiogenic edema, with transudation of fluid to the interstitial space of the lungs due to an increase in negative intrathoracic pressure secondary to obstruction of the upper airways. This is the case of a healthy patient who underwent general anesthesia and developed acute pulmonary edema after extubation. CASE REPORT: A 23-year old female patient, physical status ASA II, underwent gynecologic videolaparoscopy under general anesthesia. The procedure lasted 3 hours without intercurrence. After extubation the patient developed laryngeal spasm and reduction in oxygen saturation. The patient improved after placement of an oral cannula and administration of oxygen under positive pressure with a face mask. Once the patient was stable she was transferred to the recovery room where, shortly after her arrival, she developed acute pulmonary edema with elimination of bloody serous secretion. Treatment consisted of elevation of the head, administration of oxygen via a face mask, furosemide and fluid restriction. Chest X-ray was compatible with acute pulmonary edema and normal cardiac area. Electrocardiogram (ECG), echocardiogram and cardiac enzymes were normal. The condition of the patient improved and she was discharged from the hospital the following day, asymptomatic. CONCLUSIONS: Acute pulmonary edema associated with obstruction of the upper airways can aggravate surgical procedures with low morbidity, affecting mainly young patients. Early treatment should be instituted because it has a fast evolution and, in most cases, resolves without lasting damages. © Sociedade Brasileira de Anestesiologia, 2008.
Acute pulmonary edema associated with obstruction of the airways. Case report
Keywords: AIRWAYS: negative pressure; COMPLICATIONS: pulmonary edema; Obstruction; heart enzyme; adult; airway obstruction; case report; clinical feature; disease association; echocardiography; electrocardiography; female; human; lung edema; thorax radiography; Acute Disease; Airway Obstruction; Female; Humans; Pulmonary Edema; Young Adult